Has Scots pine (Pinus sylvestris) co‐evolved with Dothistroma septosporum in Scotland? Evidence for spatial heterogeneity in the susceptibility of native provenances. (18th July 2016) - Perry, Annika; Brown, Anna V.; Cavers, Stephen; Cottrell, Joan E.; Ennos, Richard A.
Abstract: Spatial heterogeneity in pathogen pressure leads to genetic variation in, and evolution of, disease‐related traits among host populations. In contrast, hosts are expected to be highly susceptible to exotic pathogens as there has been no evolution of defence responses. Host response to pathogens can therefore be an indicator of a novel or endemic pathosystem. Currently, the most significant threat to native British Scots pine ( Pinus sylvestris ) forests is Dothistroma needle blight (DNB) caused by the foliar pathogen Dothistroma septosporum which is presumed to be exotic. A progeny–provenance trial of 6‐year‐old Scots pine, comprising eight native provenances each with four families in six blocks, was translocated in April 2013 to a clear‐fell site in Galloway adjacent to a DNB‐infected forest. Susceptibility to D. septosporum, measured as DNB severity (estimated percentage nongreen current‐year needles), was assessed visually over 2 years (2013–2014 and 2014–2015; two assessments per year). There were highly significant differences in susceptibility among provenances but not among families for each annual assessment. Provenance mean susceptibility to D. septosporum was negatively and significantly associated with water‐related variables at site of origin, potentially due to the evolution of low susceptibility in the host in response to high historical pathogen pressure.